Cu-bearing stainless steel reduces cytotoxicity and crystals adhesion after ureteral epithelial cells exposing to calcium oxalate monohydrate - Zhiqiang Cao (Nature Portfolio, 2018)
Abstract Calcium oxalate monohydrate (COM), which is the main component of encrustation, may result in cell membrane injury. In addition, cellular damage is suggested to be the primary event attributing to COM crystal binding. To study the interaction between cells and crystals after incubating with a Cu-bearing stainless steel (316L-Cu SS), MTS and flow cytometric analyses were used to assess the cellular responses. The results confirmed that 316L-Cu SS could inhibit cytotoxicity and cellular apoptosis of ureteral epithelial cells (UECs) after COM treatment. Furthermore, molecular expressions of Cu/Zn superoxide dismutase (CuZnSOD), which were evaluated by western blot analysis and real-time quantitative PCR (qPCR), indicated that 316L-Cu SS could inhibit the oxidative stress attributing to up-regulating of CuZnSOD. Moreover, the crystal adhesion cytokine CD44 was examined with western blot and qPCR, and the corresponding hyaluronic (HA) secreted into the medium was measured by enzyme-linked immunosorbent assay (ELISA). All results were confirmed that the expressions of cells cultured with 316L-Cu SS were down-regulated, demonstrating the inhibitory performance of 316L-Cu SS against crystal adhesion.